2008
DOI: 10.1123/jsm.22.4.410
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Brand Cohesiveness and Sport Identification on Brand Fit in a Sponsorship Context

Abstract: This investigation analyzed the effects of sport identification and brand cohesiveness as predictors of brand fit in a unique sponsorship context by examining consumer responses to event sponsorships of the Dew Action Sports Tour. An additional focus of this research endeavor assessed the impact of brand fit on two important consumer behavioral outcomes: attitude toward sponsors and purchase intentions. Data were collected from 552 attendees at the Louisville, Kentucky stop of the Dew Action Sports Tour. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
138
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(165 citation statements)
references
References 54 publications
(83 reference statements)
21
138
0
6
Order By: Relevance
“…However, the researchers targeted only CFC supporter clubs, which, per this study's invariance results, are homogenous groups that would not cast doubt on the validity of the research findings. Moreover, this study's sport fans displayed strong awareness, fit, attitude, and purchase intentions levels toward the sponsor across every analyzed country, which is in concordance with other sport sponsorship studies that have examined highly identified sport fans (e.g., Alexandris et al, 2012;Biscaia et al, 2013;Gwinner & Bennett, 2008). Fifth, the current study considered only five variables, and other variables may help to further explain sponsorship effectiveness.…”
Section: Limitations and Future Researchsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the researchers targeted only CFC supporter clubs, which, per this study's invariance results, are homogenous groups that would not cast doubt on the validity of the research findings. Moreover, this study's sport fans displayed strong awareness, fit, attitude, and purchase intentions levels toward the sponsor across every analyzed country, which is in concordance with other sport sponsorship studies that have examined highly identified sport fans (e.g., Alexandris et al, 2012;Biscaia et al, 2013;Gwinner & Bennett, 2008). Fifth, the current study considered only five variables, and other variables may help to further explain sponsorship effectiveness.…”
Section: Limitations and Future Researchsupporting
confidence: 84%
“…The online survey included items adapted from previously validated surveys to measure five areas: sponsorship awareness via unaided recall (Walsh, Kim, & Ross, 2008), sponsorship fit (Gwinner & Bennett, 2008), attitude toward the sponsors (Gwinner & Bennett, 2008), gratitude (Palmatier et al, 2009), and purchase intentions (Gwinner & Bennett, 2008). Slight modifications were made to suit the specific needs of this study.…”
Section: Methodsmentioning
confidence: 99%
“…The online survey included items adapted from previously validated instruments to measure three constructs: attitude toward the sponsor (Gwinner & Bennett, 2008), gratitude (Palmatier et al, 2009), and purchase intentions (Gwinner & Bennett, 2008;Hong, 2011). Slight modifications were made to suit the specific needs of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Gwinner and Bennett 2008 [60] The fit between the sponsor and the sponsored sports event has a positive influence on consumers' purchase intensions. Herrmann et al…”
Section: Firmmentioning
confidence: 99%
“…Since the 20th century, sponsoring and its effectiveness has been one of the major issues in studies on sports marketing. Much of the interest in research towards sponsoring has been focused on brand awareness, brand image, brand positioning, and consumer attitudes [60]. The literature has clearly shown the positive effects of sponsorship on company brands and brand equity [49].…”
Section: Brands and Sponsorship As Value Creatorsmentioning
confidence: 99%